TRANSFORMASI DIGITAL: IMPLEMENTASI DAN INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN - Fasa Dwi Lestari; Moh Rofiqi (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of digital transformation policies in educational institutions and examine technology integration in the learning process. The research employs a qualitative approach with a case study method, utilizing observation, interviews, and documentation involving teachers and students. The findings reveal that although digital facilities and policies are adequately available, technology utilization remains suboptimal and tends to function merely as a medium for conventional content delivery. The integration of technology with specific instructional objectives is still limited, significantly influenced by a lack of teachers’ pedagogical-digital competencies. Conversely, students demonstrate high enthusiasm and interest in technology-based learning environments. These findings indicate a critical need for continuous teacher professional development and stronger institutional policies to ensure that technology utilization becomes more effective, innovative, and meaningful in enhancing learning quality. Therefore, shifting from mere digitalization to true digital transformation requires a holistic approach involving curriculum redesign and competency enhancement. This research contributes to the discourse on educational technology by highlighting the gap between policy availability and classroom execution, suggesting that infrastructure alone is insufficient without corresponding human resource readiness.